2020
DOI: 10.21203/rs.3.rs-107670/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated Transcriptome and Proteome Analysis Reveals Complex Regulatory Mechanism of Cotton in Response to Salt Stress

Abstract: BackgroundSoil salt stress seriously restricts the yield and quality of cotton worldwide. To investigate the molecular mechanism of cotton response to salt stress, a main cultivated variety Gossypium hirsutum L. acc. Xinluzhong 54 was used to perform transcriptome and proteome integrated analysis. ResultsThrough transcriptome analysis of cotton treated with salt stress for 0 h (T0), 3 h (T3) and 12 h (T12), we identified 8,436, 11,628 and 6,311 differentially expressed genes (DEGs) inT3 / T0, T12 / T0 and T12 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The 3 MdCER1 genes were located on 3 out of 17 chromosomes in the apple genome. As predicted, common motifs were shared in the MdCER1 gene family and MdCER1-1 and MdCER1-2 share a common conservative motif, which indicated that they may have common biological functions [22]. Plants often involve complex regulatory mechanisms in response to biotic and abiotic stresses [23].…”
Section: Discussionmentioning
confidence: 64%
“…The 3 MdCER1 genes were located on 3 out of 17 chromosomes in the apple genome. As predicted, common motifs were shared in the MdCER1 gene family and MdCER1-1 and MdCER1-2 share a common conservative motif, which indicated that they may have common biological functions [22]. Plants often involve complex regulatory mechanisms in response to biotic and abiotic stresses [23].…”
Section: Discussionmentioning
confidence: 64%